Música no novo ensino médio: um estudo de caso na Escola Estadual Governador Milton Campos - Tauini Mauê Santos Rosa (2022)
The main objective of this research is to understand the meanings of music in the Novo Ensino Médio (Lei nº 13.415/2017) of the Escola Estadual Governador Milton Campos from the formation of the Banda Central in the context of Ensino Médio em Tempo Integral - EMTI. The Banda Central is the object of the case study. The research methodology includes the analysis of official documents referring to public education policies for this segment, semi-structured interviews with students participating in the Banda Central, current vice-director and current coordinator of comprehensive education at the School, and empirical data from the observations carried out in the field prior to the pandemic. The results revealed that the meanings of music in the Novo Ensino Médio of Estadual Central occur from the relationship between music and socialization, musical learning processes in the Banda Central and the importance of music in the education of young people. It was concluded, therefore, that there is presence of informally structured musical practices through the role of young people in the structuring of repertoires and organization of the Banda's rehearsals. For young people, the Banda represents the space that enables collective musical practice and the improvement of their technical and musical knowledge. This study aims to contribute to the understanding of the meanings of musical practices of young people in the context of Novo Ensino Médio (Lei nº 13.415/17) and the place that music occupies in the education of young people in this segment.